Histopathological and Biochemical study of the effect of Citrullus colocynthis on the heart and liver of mature male rabbits: as a model for mammals: Saad S. Al-Dujaily1.Alaa Khani2, Fetiwa Manwar3 , and Salam H.Ibraim4 - Al-Dujaily, Saad S. (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of the present work is to found out if there are histopathological and enzymatic effects on the heart and liver after oral administration of Citrullus colocynthis (CC) fruit (bitter apple) for mature male rabbits, as a model for mammals. Two experiments were performed for sixty mature male rabbits that equally and randomly divided into six groups each containing five animals .In the two experiments ,independently, three groups in each one were considered as treated groups and represented as T1, T2 and T3 groups .These rabbits groups were orally administrated with low dosage of CC (4.8mg/kg/day,experiment No.1 ) and double dosage of CC extract (9.6mg /kg /day , experiment No2 ) for three intervals 2, 4 and 8 weeks ,respectively. The other three groups in each experiment were considered control and represented as C1, C2 and C3 groups, respectively. All the rabbits in control groups were given orally distilled water (DW) at the same periods of treated groups. Histopathological changes of the heart and liver with related enzymes namely; serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT) and creatinine kinase (SCK) were studied.The histopathological study revealed no changes in rabbit’s heart tissue particularly after treatment with 4.8mg/kg/day of CC for 2 and 4 weeks. While no histopathological changes were observed in the heart of rabbit groups treated with 9.6mg/kg/day of CC extract after 2 weeks. The results of the treatment with the two dosages of the CC for 8 weeks indicated a mild degenerative changes and mild necrosis of the myocardial cells. There was swelling of the hepatocytes and perivascular cuffing of mononuclear inflammatory cells after two weeks of daily treatment with 4.8mg/kg/day of CC exposure. After four weeks with the low dosage of the CC extract, caused initiation of necrosis, more inflammation picture of liver portal tract with sinusoid All rabbit groups showed statistically a significant gradual increase (P<0.05) in the value of serum enzyme GOT, GPT and CK levels after treatment with the two dosages of CC at the end of each different period compared with before treatment and control group. Concluded from this study that the dosage 4.8mg/Kg/day of CC plant resulted in simple histopathological effects on the heart and mild histopathological changes on the liver during the entire period of the study, instead of serum enzymatic elevation of SGOT ,SGPT and SCK. Further studies are recommended to found out the possibility to use and effects of CC on animal hygiene and reproduction